Use of phenyl isothiocyanate for biofilm prevention and control - Ana Cristina Abreu (2014)
The purpose of the present study was to assess the antibacterial activity of phenyl isothiocyanate (PITC), a synthetic isothiocyanate, on biofilms of Escherichia coli and Staphylococcus aureus. The effects of PITC on bacterial free energy of adhesion and motility were also investigated. Biofilm formation in 96-well polystyrene microtiter plates was quantified by crystal violet staining and the metabolic activity of those biofilms was assessed with alamar blue. The viability and culturability of the biofilm bacteria after exposure to PITC were determined. The highest removal and metabolic activity reduction of biofilms with PITC was around 90% for both bacteria. Treatment with PITC enabled 4.5 and 4.0 log(10) reductions of the number of viable cells for E. coli and S. aureus, respectively; and no colony forming units (CFUs) were detected. PITC also affected the adhesion process and motility of bacteria, greatly preventing biofilm formation. In conclusion, PITC enabled both biofilm prevention and control, promoting high biofilm removal and inactivation activities, suggesting that this compound is a promising disinfectant.